Total Sialic Acid Concentrations as a Supporting Marker of Malignancy in Acute Lymphoblastic Leukemia - Sulaiman, Gh. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
To follow  up the  response of  acute  lymphoblastic  leukemic(ALL)   patients   to   chemotherapy   treatment   and  for   prognosis, diagnosis,  the total Sialic acid  (TSA) levels was studied as a tumor marker. The study included 40 patients (male = 22, female =18) with (ALL)   were   tested   for   the   serum   and   leukocytes   homogenate concentrations  of total sialic acid (TSA)  before and after  treatment with    six   different   chemotherapy   protocols.                      While   significantly increased ( P< 0.001  ) as compared to the heal thy individuals group, serum   and   leukocytes  homogenate   TSA   concentrations   dropped significantly   (   P